2007
DOI: 10.1210/en.2007-0442
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin/Leptin Interactions in the Control of Food Intake in Rats

Abstract: Recent evidence suggests that the peptide hormone prolactin (PRL) modulates energy balance through a number of mechanisms, including acting in the brain to increase food intake. In the current studies, we first demonstrated that chronic infusions of PRL into the lateral ventricles increased food intake in cycling rats without disrupting estrous cyclicity. In subsequent experiments the hypothesis that at least part of PRL's ability to increase food intake resulted from PRL-induced leptin resistance was tested. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 49 publications
3
76
0
1
Order By: Relevance
“…However, the lack of a BAT-independent correlation between prolactin and milk production (Fig.5) contradicts the accumulated evidence that circulating prolactin re-enters the brain, interacts with distinct populations of hypothalamic neurons that express prolactin receptors (Grattan and Kokay, 2008) and acts in female rats to induce and maintain hyperphagia (Woodside, 2007). Some of these prolactin-responsive neurons co-express leptin receptors, suggesting that prolactin and leptin in rats may act together to regulate food intake (Naef and Woodside, 2007). The discrepancy between our results and the previous research may be due to either differences between animal models (mice versus rats) or differences in the blood sampling protocols.…”
Section: Leptin and Prolactin As Correlates Of Milk Productionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, the lack of a BAT-independent correlation between prolactin and milk production (Fig.5) contradicts the accumulated evidence that circulating prolactin re-enters the brain, interacts with distinct populations of hypothalamic neurons that express prolactin receptors (Grattan and Kokay, 2008) and acts in female rats to induce and maintain hyperphagia (Woodside, 2007). Some of these prolactin-responsive neurons co-express leptin receptors, suggesting that prolactin and leptin in rats may act together to regulate food intake (Naef and Woodside, 2007). The discrepancy between our results and the previous research may be due to either differences between animal models (mice versus rats) or differences in the blood sampling protocols.…”
Section: Leptin and Prolactin As Correlates Of Milk Productionmentioning
confidence: 89%
“…Circulating levels of prolactin during lactation are typically high and depend on the intensity and duration of suckling (Mattheij et al, 1979;Chan and Swaminathan, 1990). Both suppression of leptin and induction of prolactin have been suggested to contribute to lactational hyperphagia, facilitating milk production (Crowley et al, 2004;Naef and Woodside, 2007;Woodside, 2007;Smith et al, 2010). Importantly, both of these hormones have also been demonstrated to modify the gene and protein expression of UCP1 in BAT (Chan and Swaminathan, 1990;Pearce et al, 2003;Cannon and Nedergaard, 2004;Xiao et al, 2004;Cui et al, 2011).…”
Section: Leptin and Prolactin As Correlates Of Milk Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies also indicate that prolactin or placental lactogens contribute to the metabolic changes typically observed during pregnancy, such as the increase in food intake and adiposity. These studies showed that central prolactin infusions induce a leptin resistance state that changes the metabolism towards a positive energy balance (35,36). Indeed, several populations of leptin receptorexpressing neurons in mice are directly responsive to prolactin (37).…”
Section: The Hypothalamus As a Target Of Prolactin To Modulate Severamentioning
confidence: 99%
“…In pregnant rodents, central administration of leptin results in reduced food intake until mid-pregnancy when central resistance to leptin develops (Johnstone & Higuchi 2001, Mistry & Romsos 2002. In addition to an increase in plasma leptin-binding activity seen in pregnant rats (Seeber et al 2002), progesterone, prolactin, and placental lactogen may also contribute to leptin resistance (Grueso et al 2001, Naef & Woodside 2007, Brunton & Russell 2008. The development of hyperleptinemia and leptin resistance during pregnancy has been proposed to be a compensatory mechanism to allow for increased appetite and food intake to meet the energy needs of the developing fetus (Brunton & Russell 2008).…”
Section: Pregnancymentioning
confidence: 99%